Jerusalem, Israel/Palästina: Bi-nationale Tagung „Quo vadis ‚Biblical Archaeology‘? Past, Present and Future of Archaeology in the Southern Levant“ - Soennecken, Katja; Serr, Marcel (e-Forschungsberichte des DAI, 2023)
The 50th anniversary of German-Israeli diplomatic relations provided an unique opportunity to reflect the history, the current state and the future of German and German-Israeli archaeology in Israel, in the context of the bilateral relations. The GPIA hosted an interdisciplinary German-Israeli workshop dedicated to graduate students working on various subjects in several disciplines that are connected to the Ancient Near East. The aim was not only an interdisciplinary exchange of scientific knowledge between different fields, but also to increase and encourage contact and discussion between young German and Israeli researchers working on different aspects of the Ancient Near East. The conference was held in Jerusalem at the Hebrew University and the German Protestant Institute (“Kaisersaal” adjacent to Church of Ascension and courtyard adjacent to Church of the Redeemer) and lasted for three days. 17 presentations were given in four sessions (German-Israeli Joint Ventures in the Past, Present and Future; With Bible and Trowel? Biblical Archaeology today and future perspectives; Sites after excavation – Restoration, Conservation and Presentation; Archaeology and its Methods in Dialogue with other Sciences).